2020
DOI: 10.1002/jmv.26229
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral anterior uveitis as a part of a multisystem inflammatory syndrome secondary to COVID‐19 infection

Abstract: During the ongoing COVID‐19 pandemic, there is a global concern about patients presenting with inflammatory syndrome with variable clinical features. Colanfrancesco et al. described COVID‐19 systemic inflammatory reaction that are characterized by a life‐threatening hyper‐inflammation sustained by a cytokines storm which eventually leads to multi‐organ failure. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 11 publications
1
59
2
1
Order By: Relevance
“…In contrast to our study where Kawasaki‐like multisystem inflammatory syndrome present among children and adolescents 13 . Here, the main presenting complaint was bilateral blurry vision and rashes after 2 weeks of COVID‐19 infection whereas, in our study, only one or two patient develop inflamed red spots on mouth and tongue 13 . However, the pathophysiology of how SARS‐CoV‐2 causes Kawasaki‐like MIS‐C is unknown but it is hypothesized that COVID‐19 infection causes abundant inflammation and children with Kawasaki‐like multisystem inflammatory syndrome demonstrate a storm of inflammation in their body 6 …”
contrasting
confidence: 98%
See 1 more Smart Citation
“…In contrast to our study where Kawasaki‐like multisystem inflammatory syndrome present among children and adolescents 13 . Here, the main presenting complaint was bilateral blurry vision and rashes after 2 weeks of COVID‐19 infection whereas, in our study, only one or two patient develop inflamed red spots on mouth and tongue 13 . However, the pathophysiology of how SARS‐CoV‐2 causes Kawasaki‐like MIS‐C is unknown but it is hypothesized that COVID‐19 infection causes abundant inflammation and children with Kawasaki‐like multisystem inflammatory syndrome demonstrate a storm of inflammation in their body 6 …”
contrasting
confidence: 98%
“…Another case with a similar presentation has been reported in a 54‐year‐old patient. In contrast to our study where Kawasaki‐like multisystem inflammatory syndrome present among children and adolescents 13 . Here, the main presenting complaint was bilateral blurry vision and rashes after 2 weeks of COVID‐19 infection whereas, in our study, only one or two patient develop inflamed red spots on mouth and tongue 13 .…”
contrasting
confidence: 96%
“…Subtle cotton wool spots and microhemorrhages in retinal surface (33%). Hyper-reflective lesions in the GC and IP layers (100%) Virgo and Mohamed 3 Case report of a 37-year-old female with positive SARS-CoV-2 IgG (PCR was not performed) Case report of a 32-year-old male with positive PCR from nasopharyngeal swab Paracentral acute middle maculopathy (hyper-reflective lesion in the IP and OP layers with IN layer volume loss) Acute macular neuroretinopathy (hyper-reflective lesion in OP layer and disruption of the interdigitation zone) Bettach et al 4 Case report of a 54-year-old female with negative SARS-CoV- protection of this region, be encouraged quickly. Moreover, SARS-CoV-2 arrival in the retina through the optic nerve or hematogenous route may be an indication that the coronavirus has previously reached the brain.…”
Section: Authors (Year)mentioning
confidence: 99%
“…22 Bettach et al recently reported the case of a 54-year-old female with COVID-19 presenting bilateral anterior uveitis associated with a small focal intra-retinal hemorrhage in the left fovea. 4 As the patient had three negative polymerase chain reaction of the nasopharyngeal swabs with positive serology (SARS-CoV-2 IgG), the authors postulate that the anterior uveitis possibly was due to an MIS secondary to SARS-CoV-2 infection. 4 Thus, there is a possibility that, regardless of the arrival of SARS-CoV-2 in the retina, patients with COVID-19 may present retinal damage as part of a multiple organ dysfunction related to MIS.…”
Section: Authors (Year)mentioning
confidence: 99%
“…Besides, Bettach et al reported bilateral anterior uveitis accompanied with the diagnosis of multisystem inflammatory syndrome secondary to SARS CoV-2 infection and they claimed that the ocular inflammatory findings were related to SARS CoV-2 infection. At the same time, they emphasized that these findings are similar to the Kawasaki-like multisystem inflammatory syndrome, which develops secondary to SARS CoV-2 infection in children and adolescents ( Bettach et al, 2020 ).…”
Section: Introductionmentioning
confidence: 79%